3D flower-like NC@V2O3 constructed by nanoparticles for lithium-ion batteries. (September 2021) - Tian, Yaxiong; Wang, Gongshu; Zhu, Lin; Chen, Huaxia; Sun, Ting
Abstract: The morphology and structural engineering of V2 O3 anode of lithium-ion batteries plays a significant role in improving the energy storage performance since V2 O3 material suffers from tremendous volume changes, self-aggregation and intrinsic poor conductivity. In this work, we devise a novel 3D self-supporting N, C doped-V2 O3 (NC@V2 O3 ) composite, which consist of nanoparticles by adding urea to obtain 3D flower-like V2 O3 microspheres precursor during the annealing process. The V2 O3 microspheres self-assembled with nanosheets is fabricated by one-step solvothermal route. A possible morphological evolution mechanism of fabrication of granular NC@V2 O3 is explored by SEM and TEM. As anode in Li + batteries, NC@V2 O3 material exhibits outstanding rate performance of 227 mAh g −1 at the current density of 2 A g −1 and a reversible capacity of 272 mAh g −1 at 0.1 A g −1 after 200 cycles. Such great performance is attributed to granulated NC@V2 O3 architecture, which increasing the contact area of electrode-electrolyte and shortening Li + diffusion pathway. In addition, the doped N and C atoms can create more defects, providing electrochemical active sites and electronic conduction. The achievements of this study may provide new insight into design novel architecture of V2 O3 anode. Graphical Abstract: In this work, we devise a 3D self-supporting flower-like NC@V2 O3 consisting of nanoparticles which are synthesized by a simple solvothermal-calcination process. This integrated structure provides effective frame to inhibits self-aggregation of NC@V2 O3 nanoparticles. The NC@V2 O3 electrode exhibits outstanding rate performance for lithium storage arising from combination of novel structure and N, C-co doped. ga1 Highlights: The 3D self-supporting NC@V2 O3 consisting of nanoparticles are synthesized by a simple solvothermal-calcination process. Doping of N and C promotes morphological granulation of V2 O3 nanosheet. The granulated NC@V2 O3 exhibits excellent electrochemical performances.